Pemecahan Masalah Matematika Bentuk Soal Cerita Berdasarkan Model Polya pada Siswa Kelas VIII MTs Materi Pokok SPLDV - Novika Rahmawati; Maryono Maryono (Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2018)
One of the goals of mathematics teaching is that students have the ability to solve problems that include the ability to understand the problem, devised a mathematical model, solve the model and interpret the obtained solution. The ability of students to solve word problems needs to get serious attention due to the fact that in daily life, students do not face directly about number or numerals but they face word problem related to topics of mathematics. The purpose of this study was to describe the level of students' ability to solve word problems in the material of Linear Equation System with Two Variables (SPLDV). This research used a qualitative approach with descriptive research. Data collection techniques used were written tests, interviews, observations, and documentations. Data analysis technique used is the analysis of qualitative data with measures of data reduction, data presentation, and conclusion. Checking the validity of the data is done with perseverance observation, triangulation and checking peers. The results showed that: 1) High-ability students had excellent problem solving skills. 2) Medium-ability students had excellent problem solving abilities. 3) Students with moderate-ability problem solving ability is enough.